MAJĀZ: MESIN KREATIF “TA’WI>L IDEOLOGIS” MU’TAZILAH - Zamzam Afandi (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
One of the complex problems in Arabic semantics is the dichotomy of haqiqah and majāz (proper speech vs. figurative speech). This research aims to study the problem in Mu’tazili school, an Islamic school of speculative theology that flourished in the cities of Basra and Baghdad, both in present-day Iraq, during the 8th–10th centuries. The perspective of this school, which absolutized the unity and oneness of God, brought a consequence that Allah is ontologically different and categorically distinct from nature, humans, and material causality and the Qadīm (the Eternal). Any other than Allah, then, is transient or created, including Allah’s kalām or words. From this perspective, Mu’tazili school built their linguistics foundation, including lafadz and its meaning as well as the theory of philosophic dichotomy and majāz. The notion of majāz has been used to overcome the problems of interpretation of Qur’anic verses, which was categorized as mutasyābihāt, known only by Allah. In other words, besides its critical views, majāz, by Mu’tazili school, was a meaning producer of a text, especially the sacred one. This was in accordance their theological point of view, which was also their world of view or ru’yah kauniyah.